Monoclonal Antibodies in Next Generation Animal Nutrition: Mapping Nutrient Immune Interaction Networks in Livestock Systems - Md. Emran Hossain (International Journal of Molecular Biotechnological Research, 2026)
Sustainable livestock production is increasingly constrained by disease pressure, antimicrobial resistance, and declining feed efficiency under intensifying environmental stressors. Conventional nutritional strategies, while essential, remain insufficient to precisely regulate immune function and metabolic resilience. This review explores the emerging role of Monoclonal antibodies as advanced biologics in next generation animal nutrition, with a focus on mapping nutrient immune interaction networks in livestock systems. It synthesizes current knowledge on how nutrients modulate immune signaling pathways, including mTOR signaling pathway, NF kappa B signaling pathway, and JAK STAT pathway, and how these pathways intersect with antibody mediated immune regulation. The review further highlights the integration of monoclonal antibodies into nutritional frameworks to enhance pathogen control, regulate inflammation, and improve nutrient utilization efficiency. Particular emphasis is placed on the gut microbiota as a central mediator linking diet, immunity, and antibody driven responses. Advances in systems biology and omics technologies are discussed as tools for decoding complex nutrient immune networks and enabling precision livestock nutrition. Despite promising applications, challenges related to cost, delivery systems, scalability, and regulatory acceptance remain significant. Future directions include the development of species-specific antibody platforms, smart delivery mechanisms, and data driven modeling of immune nutritional interactions. Overall, this review positions monoclonal antibodies as transformative tools for optimizing animal health and productivity, contributing to sustainable and antibiotic reduced livestock production systems.
Keywords: Animal nutrition; gut microbiota; immune modulation; monoclonal antibodies; nutrient signaling; precision nutrition